CAPAIAN ESTETIK PROSA FIKSI INDONESIA ABAD KE-21 - Sunaryono Basuki Ks (Universitas Pendidikan Ganesha, 2010)
The birth of modern Indonesian novel can be represented by Belongs, followed by the works ofPRIMEDIA Ananta Toer and Mochtar Lubis. New style of writing has been practiced by Iwan Simatupang,Budi Darma, Danarto, and Putu Wijaya. Other authors writing in the mainstreamstyle are Umar Khayam, YB Mangunwijaya, Nh Dini, Subagio Sastrowardoyo, and many others.The 21st century is marked by the works of young writers, writing more intensely based on seriousresearch, using various materials and settings. There have been trans-gender, trans-locale, andvarious points of view. The young potential writers are Nukila Amal, Ayu Utami, Oka Rusmini, DewiLestari, Cok Sawitri, Andrea Hirata, E.S. Ito, Eka Kurniawan, Triyanto Triwikromo and many others.Their works, supported by research and serious treatment to their materials are surprisingly promising.Key words: modern Indonesian novel, mainstream style, young writers